Annual thermoeconomic analysis of a Concentrating Solar Power + Photovoltaic + Multi-Effect Distillation plant in northern Chile. (1st June 2020) - Mata-Torres, Carlos; Palenzuela, Patricia; Zurita, Adriana; Cardemil, José M.; Alarcón-Padilla, Diego-César; Escobar, Rodrigo A.
Highlights: PV integration increases the electric output but can benefit or hinder the water production. The PV plant integration allows to decrease the TCE and TCW. A pareto frontier between the TCE and TCW was obtained. In the Pareto frontier, the PV size has a trade-off with the CSP and MED size. Abstract: A detailed annual performance and thermoeconomic analysis of a Concentrated Solar Power plant coupled to a Photovoltaic and a Multi-Effect Distillation plants (CSP + PV + MED) were performed using an extensive methodology based on an hourly simulation. The aim was to assess the impact of the PV integration into the CSP + PV plant and to evaluate the sizing of the plant in terms of the design parameters (PV plant size, solar multiple, Thermal Energy Storage capacity, and numbers of MED units) that allow achieving the lowest thermoeconomic electric and water costs (TCE and TCW). Results show that PV integration mainly increases the electric output but could increase the water production depending on the PV and CSP plants' sizes. Moreover, the PV plant cost is mainly allocated to electricity, decreasing the TCE, while on the TCW it has a moderate impact. Finally, it was found that the PV plant and the CSP plant size has contradictory roles between the costs, where the minimum TCE is obtained for large PV plant with an undersized CSP plant and one MED unit, and the minimum TCW is obtained for small PV plant with an oversized CSP plant and a large MED plant (5 units).